A clinical repetitive transcranial magnetic stimulation service in Australia: 6 years on. (November 2015) - Galletly, Cherrie A; Clarke, Patrick; Carnell, Benjamin L; Gill, Shane
Objective: There is considerable research evidence for the effectiveness of repetitive transcranial magnetic stimulation in the treatment of depression. However, there is little information about its acceptability and outcomes in clinical settings. Method: This naturalistic study reports on a clinical repetitive transcranial magnetic stimulation service that has been running in Adelaide, South Australia (SA), for 6 years. During this time, 214 complete acute courses were provided to patients with treatment-resistant Major Depressive Disorder. Patients received either sequential bilateral or right unilateral repetitive transcranial magnetic stimulation treatment involving either 18 or 20 sessions given over 6 or 4 weeks respectively. Data included patient demographic details, duration of depression, and medication at the beginning of their repetitive transcranial magnetic stimulation course. The Hamilton Depression Rating Scale was used to assess response to repetitive transcranial magnetic stimulation. Results: Of those undergoing a first-time acute treatment course of repetitive transcranial magnetic stimulation ( N = 167), 28% achieved remission, while a further 12% met the criteria for a response to treatment. Most patients ( N = 123, 77%) had previously been treated with five or more antidepressant medications, and 77 (47%) had previously received electroconvulsive therapy. Referral rates remained high over the 6 years, indicating acceptance of the treatment by referring psychiatrists. There were no significant adverse events, and the treatment was generally well tolerated. In all, 41 patients (25%) had a second course of repetitive transcranial magnetic stimulation and 6 (4%) patients had a third course; 21 patients subsequently received maintenance repetitive transcranial magnetic stimulation. Conclusion: This naturalistic study showed that repetitive transcranial magnetic stimulation was well accepted by both psychiatrists and patients, and has good efficacy and safety. Furthermore, repetitive transcranial magnetic stimulation can provide a useful treatment alternative as part of outpatient mental health services for people with depression.